Quantitative profiling and pattern analysis of triacylglycerol species in Arabidopsis seeds by electrospray ionization mass spectrometry - Li, Maoyin; Baughman, Ethan; Roth, Mary R.; Han, Xianlin; Welti, Ruth; Wang, Xuemin (My University, 2014)
Plant triacylglycerols (TAGs), or vegetable oils, provide approximately 25% of dietary calories to humans and are becoming an increasingly important source of renewable bioenergy and industrial feedstocks. TAGs are assembled, by multiple enzymes in the endoplasmic reticulum, from building blocks that include an invariable glycerol backbone and variable fatty acyl chains. It remains a challenge to elucidate the mechanism of synthesis of hundreds of different TAG species in planta. One reason is the lack of an efficient analytical approach quantifying individual molecular species. Here we report a rapid and quantitative TAG profiling approach for Arabidopsis seeds based on electrospray ionization tandem mass spectrometry with direct infusion and multiple neutral loss scans. The levels of 93 TAG molecular species, identified by their acyl components, were determined in Arabidopsis seeds. Quantitative TAG pattern analyses revealed that the TAG assembly machinery preferentially produces TAGs with one elongated fatty acid. The importance of the selectivity in oil synthesis was consistent with an observation that an Arabidopsis mutant overexpressing a patatin-like phospholipase had enhanced seed oil content with elongated fatty acids. This quantitative TAG profiling approach should facilitate investigations aimed at understanding the biochemical mechanisms of TAG metabolism in plants.
Keywords: Arabidopsis thaliana; Mass spectrometry; Lipidomics; Seed oil; Triacylglycerol profiling